2020
DOI: 10.1088/1755-1315/463/1/012140
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the prototype shaftless small scale horizontal wind turbine for electricity generating from industrial exhaust air system

Abstract: Man-made or unnatural wind from the industrial exhaust air system is an alternative wind resource for countries with natural low-speed or intermittent wind such as Thailand. It has strong and consistent wind speed when compared to the natural wind, with velocity about 5 to 10 m/s at a distance of 5 cm from the exhaust air outlet. However, some negative impacts to the exhaust air system performance was observed when a conventional wind turbine was employed. The objective of this research is to feasibility study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Locating the turbine at a high point in the duct can cause the back force to reduce significantly. In the research by Wachira Puttichaem et al [100,101], the researchers suggested an efficiency of 51%, which is close to the Betz limit. From this, it is clear that housing such SSHWT within an augmentation device would increase its efficiency exponentially.…”
Section: Wind Turbine Efficiency Against the Betz Limitmentioning
confidence: 77%
See 2 more Smart Citations
“…Locating the turbine at a high point in the duct can cause the back force to reduce significantly. In the research by Wachira Puttichaem et al [100,101], the researchers suggested an efficiency of 51%, which is close to the Betz limit. From this, it is clear that housing such SSHWT within an augmentation device would increase its efficiency exponentially.…”
Section: Wind Turbine Efficiency Against the Betz Limitmentioning
confidence: 77%
“…As per the study by Chong et al [69,106], 13% of the power required by the cooling tower can be recovered. Likewise, for the study by Wachira Puttichaem et al [101], an energy recovery of 51% was obtained from the stream. In monetary terms, the savings are enormous.…”
Section: Financial Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed the idea of the shaftless horizontal axis wind turbine, 21 which created an open channel in the middle of the wind turbine using the tilted blades to release the discharge air into the environment. This design was a lab-scale test.…”
Section: Development Of the Shaftless Horizontal Axis Wind Turbine For Waste Wind Energy Recoverymentioning
confidence: 99%
“…Mann and Singh [8][9][10] advocated for augmenting velocity in industrial flue gas using appropriate diffusers, achieving remarkable velocities of 20 m/s and 57.2 m/s with VAWT configurations featuring NACA airfoils. Wachira Puttichaem et al [11,12] proposed a novel design for small scale horizontal wind turbines (SSHWT) catered towards air conditioning systems' exhaust, introducing innovative generator technology without specifying velocity increases. Lastly, Douglas Yeboah et al [13] explored the potential of underground mine exhaust for power generation, achieving a velocity of 7.67 m/s, albeit without detailed velocity augmentation strategies.…”
Section: Introductionmentioning
confidence: 99%